Wastewater Management Strategies for Reducing Drought Vulnerability and Enhancing Women’s Local Wisdom: A Case Study of Kebonharjo Village, Indonesia - Yuniarta Vuspita; RR. Susilastuti Dwi Nugrahajati; Arif Rianto Budi Nugroho; Yohana Noradika Maharani; Johan Danu Prasetya; Ficky Adi Kurniawan (Tecno Scientifica Publishing, 2026)
Prolonged drought has become a recurrent hydrometeorological disaster that significantly affects rural communities in Indonesia, particularly in areas with limited water infrastructure. In 2023, the Special Region of Yogyakarta experienced widespread drought, with severe impacts in Kulon Progo Regency, especially in Samigaluh Subdistrict. Kebonharjo Village, located in the Menoreh Hills, has faced persistent clean water shortages due to climate variability, environmental degradation, and increasing water demand. These conditions have intensified social vulnerability, especially among women, who are primarily responsible for household water management and water-dependent livelihood activities. This study aims to examine women’s multidimensional vulnerability to drought, analyze wastewater management as a form of local wisdom-based adaptation, and identify policy implications for gender-responsive disaster risk reduction. Using a qualitative case study approach, data were collected through in-depth interviews, focus group discussions, participatory observation, and document analysis from January to March 2025. Data were analyzed using the interactive model of Miles and Huberman. The findings reveal that women experience physical vulnerability due to long distances to water sources, economic vulnerability resulting from declining agricultural income and increasing household expenditures, and structural vulnerability linked to limited participation in village-level decision-making. At the same time, women demonstrate strong adaptive capacity through wastewater reuse, rotational water collection, and ecological knowledge of seasonal indicators. The novelty of this study lies in positioning wastewater management as a gendered adaptation strategy rooted in women’s local wisdom rather than merely a domestic coping practice. The study concludes that integrating women’s local knowledge into village-level drought governance and strengthening their participation in decision-making are essential for building community resilience and advancing gender-equitable disaster risk reduction.